A new salinity index for the invertebrate fauna of Australian inland waters - Bruce C. Chessman (Hydrobiologia, 2023)
Anthropogenic salinisation of inland waters worldwide causes diverse social, economic and ecological impacts, including shifts in the composition of biological communities. I used published data on occurrence of aquatic invertebrate taxa in relation to salinity to develop a novel Invertebrate-Based Salinity Index (IBSI) suitable for purposes such as indicating the ecological impact of anthropogenic salinisation and charting faunal recovery after salinity mitigation. Testing of the index with data independent of those used in its derivation showed a stronger association with salinity than prior Australian salinity indices based on macroinvertebrates. IBSI is applicable to both running and standing inland waters across Australia, and could be extended to other countries. Potential limitations of IBSI and its underlying salinity tolerance values are discussed, and suggestions are made for future index refinement and testing.

The value of artificial farm ponds to Australian eastern long-necked turtles - Bruce C. Chessman (Hydrobiologia, 2022)

Limitations of trait‐based approaches for stressor assessment: The case of freshwater invertebrates and climate drivers - Anna T. Hamilton; Ralf B. Schäfer; Matthew I. Pyne; Bruce Chessman; Karan Kakouei; Kate S. Boersma; Piet F. M. Verdonschot; Ralf C. M. Verdonschot; Meryl Mims; Kieran Khamis; Britta Bierwagen; Jen Stamp (Global Change Biology, 2020)
The appeal of trait‐based approaches for assessing environmental vulnerabilities arises from the potential insight they provide into the mechanisms underlying the changes in populations and community structure. Traits can provide ecologically based explanations for observed responses to environmental changes, along with predictive power gained by developing relationships between traits and environmental variables. Despite these potential benefits, questions remain regarding the utility and limitations of these approaches, which we explore focusing on the following questions: (a) How reliable are predictions of biotic responses to changing conditions based on single trait–environment relationships? (b) What factors constrain detection of single trait–environment relationships, and how can they be addressed? (c) Can we use information on meta‐community processes to reveal conditions when assumptions underlying trait‐based studies are not met? We address these questions by reviewing published literature on aquatic invertebrate communities from stream ecosystems. Our findings help to define factors that influence the successful application of trait‐based approaches in addressing the complex, multifaceted effects of changing climate conditions on hydrologic and thermal regimes in stream ecosystems. Key conclusions are that observed relationships between traits and environmental stressors are often inconsistent with predefined hypotheses derived from current trait‐based thinking, particularly related to single trait–environment relationships. Factors that can influence findings of trait‐based assessments include intercorrelations of among traits and among environmental variables, spatial scale, strength of biotic interactions, intensity of habitat disturbance, degree of abiotic stress, and methods of trait characterization. Several recommendations are made for practice and further study to address these concerns, including using phylogenetic relatedness to address intercorrelation. With proper consideration of these issues, trait‐based assessment of organismal vulnerability to environmental changes can become a useful tool to conserve threatened populations into the future.

Water Regimes and Macroinvertebrate Assemblages in Floodplain Wetlands of the Murrumbidgee River, Australia - Bruce C. Chessman; Lorraine Hardwick (Wetlands, 2014)

Biological traits predict shifts in geographical ranges of freshwater invertebrates during climatic warming and drying - Bruce C. Chessman (Journal of Biogeography, 2012)
Aim To test the ability of biological traits to predict climate‐related changes in geographical ranges of running‐water invertebrates. Location The Australian state of New South Wales and the Australian Capital Territory. Methods I analysed data from 8928 biomonitoring samples collected during a 16‐year period of generally rising air temperatures and declining precipitation. I used quantile regression to test for expansions and contractions on the climatically cooler, warmer, drier and wetter edges of the ranges of 120 invertebrate taxa, and correlated these shifts with the traits of thermophily (degree of preference for high versus low temperature) and rheophily (preference for flowing versus still water). Results The most commonly inferred range shifts were cool‐edge expansion plus warm‐edge contraction (71 taxa) and wet‐edge expansion plus dry‐edge contraction (71), but contractions from both cool and warm extremes (36) and from both dry and wet extremes (28) were also frequent. High‐temperature preference was associated with cool‐edge expansion and low‐temperature preference with wet‐edge expansion and contraction from all other extremes. A preference for flow was associated with wet‐edge expansion and dry‐edge contraction. Main conclusions Trait analysis has potential for predicting which species will expand their ranges and which will contract, but needs to be coupled with assessment of how the landscape provides each species with opportunities to track or avoid climate change. Improved quantification of climatically relevant traits and integration of trait analysis with species distribution modelling are likely to be beneficial.

Insights into Human Impacts on Streams from Tolerance Profiles of Macroinvertebrate Assemblages - Bruce C. Chessman; Paul K. McEvoy (Water, Air, & Soil Pollution, 2012)

Complex environmental gradients predict distributions of river-dependent plants in eastern Australia - Bruce C. Chessman; Meredith J. Royal (Aquatic Sciences, 2010)

Climatic changes and 13‐year trends in stream macroinvertebrate assemblages in New South Wales, Australia - BRUCE C. CHESSMAN (Global Change Biology, 2009)
Over the period from 1994 to 2007, air and water temperatures in the Australian state of New South Wales (NSW) increased while rainfall and river flows declined. Data on the occurrence of stream macroinvertebrate families in bioassessment samples collected in NSW during this period were examined to see whether a biological response to these climatic and hydrological trends could be discerned. Multiple logistic regression was used to test for long‐term trends in the probability of detection of individual macroinvertebrate families within the samples, taking account of the latitude, longitude, altitude, hydraulic habitat, time of year and subsampling method associated with each sample. Of the 124 families and family groups tested, 33 had statistically significant increasing trends, 37 had significantly declining trends and 54 had no significant trend; however, many of the last group were seldom collected and their trend estimates had wide confidence limits. Significant relationships were found between the thermophily and rheophily of the families and the estimated strength and direction of their long‐term trends, with families that favour colder waters and faster‐flowing habitats more likely to have declined. Although many families showed trends of increasing detection within samples, such trends do not necessarily equate to increasing prevalence in the environment because the extent of wetted habitat has probably declined, especially flowing habitat. In addition, because of likely intrafamilial trait diversity, increasing or apparently increasing families may include species in decline. Many freshwater macroinvertebrate species in NSW may be threatened by anthropogenic climate change, exacerbated by water withdrawals. The thermal tolerances, rheophily and other pertinent traits of individual species need to be determined to identify those most at risk.

Trophic linkages between periphyton and grazing macroinvertebrates in rivers with different levels of catchment development - Bruce C. Chessman; Douglas P. Westhorpe; Simon M. Mitrovic; Lorraine Hardwick (Hydrobiologia, 2009)

Development of blooms of Cyclotella meneghiniana and Nitzschia spp. (Bacillariophyceae) in a shallow river and estimation of effective suppression flows - Simon M. Mitrovic; Bruce C. Chessman; Alec Davie; Estelle L. Avery; Natasha Ryan (Hydrobiologia, 2008)

Are River Bioassessment Methods using Macroinvertebrates Applicable to Wetlands? - Jenny Davis; Pierre Horwitz; Richard Norris; Bruce Chessman; Megan McGuire; Bea Sommer (Hydrobiologia, 2006)

Bioassessment in A Harsh Environment: A Comparison of Macroinvertebrate Assemblages at Reference and Assessment Sites in An Australian Inland River System - Bruce C. Chessman; Lisa A. Thurtell; Meredith J. Royal (Environmental Monitoring and Assessment, 2006)

Rapid assessment of rivers using macroinvertebrates: the role of experience, and comparisons with quantitative methods - Leon Metzeling; Bruce Chessman; Rodney Hardwick; Vera Wong (Hydrobiologia, 2003)

Towards diagnostic biotic indices for river macroinvertebrates - Bruce C. Chessman; Paul K. McEvoy (Hydrobiologia, 1997)